2021
DOI: 10.3176/oil.2021.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of kerogen oxidative dissolution in subcritical water using oxygen from air

Abstract: Society's growing demands on everyday products and materials are increasingly difficult to meet in an environment that seeks to avoid petroleumbased processes. Instead of abandoning fossil materials altogether, more research should be done on their efficient and clean conversion. One option for this is the oxidative dissolution of kerogen in water under conditions that satisfy the subcritical range (T = 150-200 °C, pO 2 = 0.5-4 MPa). The resulting mixture contains a substantial amount of various aliphatic carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The idea is based on the knowledge that the organic structure of kukersite kerogen contains compounds with widely varying oxidation potentials. The authors of this paper have shown repeatedly that methylresorcinols are far more sensitive towards air oxidation than the rest of the kerogen or formed dicarboxylic acids due to the increased electron density on the aromatic ring [20,23]. If oxidized as single compounds, methylresorcinols are decomposed into CO 2 within 1 hour at 175 °C with pO 2 20 bar, together with the formation of acetic acid, formic acid and butanoic acid [24].…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…The idea is based on the knowledge that the organic structure of kukersite kerogen contains compounds with widely varying oxidation potentials. The authors of this paper have shown repeatedly that methylresorcinols are far more sensitive towards air oxidation than the rest of the kerogen or formed dicarboxylic acids due to the increased electron density on the aromatic ring [20,23]. If oxidized as single compounds, methylresorcinols are decomposed into CO 2 within 1 hour at 175 °C with pO 2 20 bar, together with the formation of acetic acid, formic acid and butanoic acid [24].…”
Section: Introductionmentioning
confidence: 91%
“…Calculations were made using experimental data from previous publications [19,20]. In these experiments, oil shale with the organic content enriched to 70% was used (hereafter referred to as K-70).…”
Section: Oil Shale Oxidationmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with the demonstration by Liu et al 24 and Wu et al 25 through experiments. In addition, under the conditions of subcritical water 26 , 27 , water vapor 13 , 28 and nitrogen 29 , 30 , the evolution of pore structure of oil shale has been studied, but under the conditions of high pressure, the influence mechanism of pore structure evolution on the coking and product release behavior of shale oil is less studied. To sum up, the effects of environmental atmosphere, temperature and pressure on oil shale pyrolysis have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%